2017
DOI: 10.1183/13993003.00471-2017
|View full text |Cite
|
Sign up to set email alerts
|

A virtual asthma clinic for children: fewer routine outpatient visits, same asthma control

Abstract: eHealth is an appealing medium to improve healthcare and its value (in addition to standard care) has been assessed in previous studies. We aimed to assess whether an eHealth intervention could improve asthma control while reducing 50% of routine outpatient visits.In a multicentre, randomised controlled trial with a 16-month follow-up, asthmatic children (6-16 years) treated in eight Dutch hospitals were randomised to usual care (4-monthly outpatient visits) and online care using a virtual asthma clinic (VAC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 32 publications
0
56
0
Order By: Relevance
“…The 8 hospitals originally participating in the randomized controlled trial (RCT) [ 11 ] were approached to also collaborate in this study. Of these, 6 hospitals agreed to participate, and 2 hospitals declined for logistic reasons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 8 hospitals originally participating in the randomized controlled trial (RCT) [ 11 ] were approached to also collaborate in this study. Of these, 6 hospitals agreed to participate, and 2 hospitals declined for logistic reasons.…”
Section: Methodsmentioning
confidence: 99%
“…After 16 months of follow-up, the number of symptom-free days and the degree of asthma control improved in children who received care using the VAC, and we concluded that routine outpatient visits could partly be replaced by monitoring asthmatic children using eHealth. [ 11 ] Furthermore, the outcome of the cost-effectiveness analysis was in favor of using Web-based monitoring as a substitution for outpatient visits from a health economics perspective [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveal that although overall satisfaction with telehealth encounters is high in patients, a significant minority still prefer face to face consultations [5][6][7]. There is early evidence showing that telehealth care is as effective as in person care when treating chronic conditions like childhood asthma [8,9]. While telehealth technology is rapidly improving technological limitations still lead to suboptimal and frustrating provider-patient telehealth interactions [6,7].…”
Section: Clinical Medicine and Telehealthmentioning
confidence: 99%
“…eHealth is a catch-all concept of care using home monitoring devices, communication tools, and ambulatory ICT to organize care. Despite recent validations of eHealth strategies and devices for use at home (14) and the promising results of a few eHealth studies conducted in childhood asthma (13,15), the actual uptake of eHealth programs into daily clinical practice is scarce. Published eHealth studies are difficult to compare due to heterogeneity in study endpoints and designs which are usually specifically tailored to healthcare systems and cultural backgrounds.…”
Section: Discussion Implementation Considerations: What Covid-19 Taugmentioning
confidence: 99%